Pemberdayaan Pelaku UMKM Desa Mangli Kecamatan Kaliangkrik dalam Pengembangan Promosi Melalui E-Commerce - Gabriel Eksousia Oktaf; Noval Dimas Saputra; Faiz Achmad Alauddin; Dita Cahya Puspitaningrum (Jurnal Bina Desa, 2026)
The advancement of digital technology has created new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their markets through e-commerce. However, many MSMEs in remote areas, such as Mangli Village, face challenges in utilizing this technology due to low digital literacy and limited resources. This article examines the empowerment efforts of MSME actors in Mangli Village through training and mentoring in using e-commerce as a promotional tool. Using a descriptive qualitative method, this activity involved observation, interviews, and direct training for MSME actors. The results indicate that this empowerment successfully enhanced the digital capabilities of MSME actors, expanded market reach, and improved the competitiveness of local products. The use of e-commerce proved effective in helping MSMEs in Mangli Village reach a broader market and increase revenue.